Major depressive disorder and current psychological distress moderate the effect of polygenic risk for obesity on body mass index - Clarke, T-K; Hall, L S; Fernandez-Pujals, A M; MacIntyre, D J; Thomson, P; Hayward, C; Smith, B H; Padmanabhan, S; Hocking, L J; Deary, I J; Porteous, D J; McIntosh, A M (Translational psychiatry, 2015)
Major depressive disorder (MDD) and obesity are frequently co-morbid and this correlation is partly due to genetic factors. Although specific genetic risk variants are associated with body mass index (BMI) and with larger effect sizes in depressed individuals, the genetic overlap and interaction with depression has not been addressed using whole-genome data. Polygenic profile scores for MDD and BMI were created in 13 921 members of Generation Scotland: the Scottish Family Health Study and tested for their association with BMI, MDD, neuroticism and scores on the General Health Questionnaire (GHQ) (current psychological distress). The association between BMI polygenic profile scores and BMI was tested fitting GHQ, neuroticism or MDD status as an interaction term to test for a moderating effect of mood disorder. BMI polygenic profile scores were not associated with lifetime MDD status or neuroticism although a significant positive association with GHQ scores was found ( P =0.0001, β =0.034, r 2 =0.001). Polygenic risk for MDD was not associated with BMI. A significant interaction between BMI polygenic profile scores and MDD ( P =0.0003, β =0.064), GHQ ( P =0.0005, β =0.027) and neuroticism ( P =0.003, β =0.023) was found when BMI was the dependent variable. The effect of BMI-increasing alleles was greater in those with MDD, high neuroticism or current psychological distress. MDD, neuroticism and current psychological distress amplify the effect of BMI polygenic profile scores on BMI. Depressed individuals with a greater polygenic load for obesity are at greater risk of becoming obese than control individuals.